GAYA KEPEMIMPINAN CAMAT DALAM MENINGKATKAN KINERJA PEGAWAI KANTOR KECAMATAN SARUDU KABUPATEN MAMUJU UTARA PROVINSI SULAWESI BARAT - Tarmizi, Adi; Pasinringi, Andi; Khairil, Muhammad (Katalogis, 2019)
This research aims to find out the leadership style of districkt head of Sarudu districkt of north Mamuju Regency. Data saken were primary and secondary data. The data were collected through observation, interview, and documentation. To complete the data of the research, the researcher used 6 informants. The research used theory adapted from S. Pamudji to measure the leadhership style of the district head at Sarudu district office. The research results reveal that the leadership style of the district head at the district office tends to use motivation style, Seen from the results that overal it is almost maximal but yet have not fulfilled economy needs of the employeesÂ  of the office, Besides, there is also a controlling style from the district head to his head is more dominant to situasional than autocratic.